What's new in molecular genetic pathology 2021: solid tumors and NGS panel selection - Guoli Chen; Patricia C. Tsang (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
The linchpin of precision medicine is molecular genetic and genomic testing. Molecular biomarkers are important for establishing precise diagnoses and for predicting therapeutic responses that enable cancer patients to receive personalized and targeted treatment. Below are highlights of the current considerations in next generation sequencing (NGS) panel selection, and in molecular testing of solid tumors of the lung, digestive system, thyroid and soft tissue.